Research on Radial Motion Characteristic of the Cropping Hammer in Radial-Forging Cropping Method - Lijun Zhang; Shengdun Zhao; Zhenwei Wang (Advances in Materials Science and Engineering)
The radial loading form applied to the bar is very important for reducing or avoiding the impact and vibration of the radial-forging cropping system and obtaining the high-quality cross section. A new radial stroke loading curve of the cropping hammer based on the cycloid form is proposed and the dynamic model of radial stroke loading mechanism is built. With the aim of obtaining the equivalent stiffness of the bar with V-shaped notch, which is a key parameter affecting the dynamic characteristic of radial stroke loading mechanism, the analytic model of the bar is built and the simulation experiments are designed by means of the orthogonal test method. The analytical results show that the diameter of the bar has the significant influence on the equivalent stiffness of the bar. Furthermore, the equivalent stiffness of the bar with V-shaped notch can be directly calculated according to the equivalent stiffness of smooth bar when h/d<0.05 and r>0.15. By using the cycloid stroke curve, the cropping experimental results for 45 steel bars and 20 steel bars show that the radial impact and vibration of the cropping system are decreased and the bar cross-section qualities have been significantly improved.